Analysis of Railway Track Type Selection on the Lahat-Lubuklinggau Line - Windi Nopriyanto; Septiana Widi Asuti; Puspita Dewi; Sapto Priyanto (Jurnal Indonesia Sosial Teknologi, 2024)
Currently, the railway line from Lahat to Lubuklinggau uses the R.42 rail type with a crossing power capacity of 2,106 > 5,106 tons/year. An increase in road class is needed to increase crossing capacity. This research aims to determine the feasibility and impact of upgrading the rail type from R.42 to R.54 to improve the operational efficiency and safety of the Lahat-Lubuklinggau railway line. In this study, the author uses the railway loading method using the beam on the elastic foundation (BoEF) concept to calculate rail permit voltage to ensure that the capacity of the railroad can accommodate the load of railway traffic. The study results in show that with the upgrade of the railroad class to class III with the R.54 rail type, this line can transport a load of 5,924,001.60 tons/year, an increase from 1,838,390.40 tons/year. In addition, the track with the R.54 rail type also meets the requirements for trains with the largest load, considering that the allowable voltage (1,097.18 kg/cm²) is smaller than the previous rail allowable voltage (1,738.14 kg/cm²). It is estimated that the R.54 rail type has a life resistance of 16-17 years against crossing power without the Babaranjang train and for 9-10 years against crossing power with the Babaranjang train for the coming year.